2015
DOI: 10.1021/acs.orglett.5b02820
|View full text |Cite
|
Sign up to set email alerts
|

Carbenylative Amination and Alkylation of Vinyl Iodides via Palladium Alkylidene Intermediates

Abstract: Most palladium-catalyzed reactions involving insertion of alkylidenes with α-hydrogens undergo β-hydride elimination from alkylpalladium(II) intermediates to form alkenes. Vinyl iodides were shown to generate η(3)-allylpalladium intermediates that resist β-hydride elimination, preserving the sp(3) center adjacent to the carbene moiety. Acyclic stereocontrol (syn/anti) for carbenylative amination and alkylation reactions was low, suggesting a lack of control in the migratory insertion step. Highly hindered carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…218 In addition, they could also achieve the use of N-tosylhydrazones 363 as carbene precursors in a threecomponent reaction by using benzyltriethylammonium chloride as the phase transfer catalyst (PTC) and lithium tert-butoxide as the base, giving simple allylamine 364 as the product. 219 Again, the nucleophilic substitution process occurred in high regioselectivity, which was presumably controlled by the steric hindrance of the carbene moiety. The vinyl iodides in the Zconfiguration worked better in these transformations than those in the E-configuration (Scheme 63c).…”
Section: Cascade Process Of the Coupling Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…218 In addition, they could also achieve the use of N-tosylhydrazones 363 as carbene precursors in a threecomponent reaction by using benzyltriethylammonium chloride as the phase transfer catalyst (PTC) and lithium tert-butoxide as the base, giving simple allylamine 364 as the product. 219 Again, the nucleophilic substitution process occurred in high regioselectivity, which was presumably controlled by the steric hindrance of the carbene moiety. The vinyl iodides in the Zconfiguration worked better in these transformations than those in the E-configuration (Scheme 63c).…”
Section: Cascade Process Of the Coupling Productsmentioning
confidence: 99%
“…223 Van Vranken and co-workers further demonstrated that aliphatic aldehyde derived N-tosylhydrazones were also suitable carbene precursors, which afforded the corresponding products 372 in good yield with high regioselectivity (Scheme 64c). 219 In 2013, Liang and co-workers found that the π-allyl palladium species generated from the combination of aryl iodides with α,βunsaturated aldehyde derived N-tosylhydrazones could also be trapped by carbon nucleophiles, affording the three-component coupling products 373 in moderate to good yields. 224 In this reaction, the nucleophilic attack occurs regioselectively at the distal position of the aryl group in the case of (E)-but-2-enalderived N-tosylhydrazones (R = Me), providing the products bearing styrene-type structures.…”
Section: Cascade Process Of the Coupling Productsmentioning
confidence: 99%
“…The η 1 -allyl­palladium complex could generate η 3 -allyl­palladium intermediate E , which could be trapped by sulfinic acid salt and give 3 as the only product. The selectivity is consistent with previous reports …”
Section: Resultsmentioning
confidence: 99%
“…Wang, we, and Sekar have reported interception of the η 3 -oxo­allyl­palladium intermediate with a double bond for the construction of cyclic architectures or it can also be trapped by a nucleophile . We reported that the Pd-catalyzed insertion of an α,β-unsaturated diazo compound could access the η 3 -allyl­palladium intermediates that would then be attacked by amines, enolates, and sulfinic acid salt. , Van Vranken, Wang, and we have explored the Pd-catalyzed reactions of vinyl halides with N -tosylhydrazone to generate η 3 -allylpalladium species, which can be trapped by amines, oxygen or enolates (Scheme a–c) . However, in the Pd-catalyzed cross-coupling reaction of vinyl halides with N -tosylhydrazone, sulfinic acid salt was generated as a byproduct.…”
Section: Introductionmentioning
confidence: 99%
“…Both indane and tetraline derivatives can be synthesized using this transformation, in which a 5-exo-trig or 6-exo-trig cyclization is involved in the formation of the second C–C bond, respectively (Scheme b). When the substitution occurs at the other side of the allylic moiety, two C–C bonds can be constructed, but not on the same carbon. , …”
Section: Ketones and Aldehydes As Amphiphiles To Build Two C–c Bondsmentioning
confidence: 99%